2021
DOI: 10.18502/ccb.v2i2.7396
|View full text |Cite
|
Sign up to set email alerts
|

Blenderized Tube Feeding in Pediatric Patients: A Systematic review

Abstract: Background: Enteral feeding (EF) is the delivery of liquid nutritional support through a tube for hospitalized patients with gastrointestinal dysfunction who are incapable of eating or unable to meet their nutritional requirements via the oral route. Hospitals’ reports indicate an increased interest and demand for blenderized tube feeding (BTF) as an alternative to commercial enteral formulas particularly in families of tube fed children. In particular, by increasing food sensitivity and more complex identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Furthermore, blended feeding can be administered safely and can meet nutrient needs if managed by a knowledgeable medical team (Bobo, 2016). Dieticians are deemed essential in supporting careful selection and suitability of individuals for blended feeding and monitoring of effect thereafter by two papers (Bahramian et al, 2021; Jeffery et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, blended feeding can be administered safely and can meet nutrient needs if managed by a knowledgeable medical team (Bobo, 2016). Dieticians are deemed essential in supporting careful selection and suitability of individuals for blended feeding and monitoring of effect thereafter by two papers (Bahramian et al, 2021; Jeffery et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is noted that not all dieticians feel confident in the process of initiating blended feeding; hence, the need for information packs and guidelines for dieticians (Bremner & Brooks, 2022). Guidelines need to address issues around not only implementation but monitoring and how to address nutritional inadequacies as suggested in two papers (Bahramian et al, 2021; Jeffery et al, 2022). In addition to guidelines, O'Sullivan et al (2019) reported the need for training and information to support dieticians in the implementation of blended feeding and suggested the efficacy of a practical training course could be investigated to assess its potential to enhance professional competency in this area.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations